2016
DOI: 10.5430/ijfr.v7n4p1
|View full text |Cite
|
Sign up to set email alerts
|

International Parity Relations and Economic Shock: Evidence from Swiss Franc Unpegging

Abstract: In this paper, we examine the association between the macroeconomic variables -interest and inflation rate, and the expected spot rate of Swiss franc against Euro around the abandonment of the ceiling on the Swiss franc by the Swiss National Bank (SNB), January 15, 2015, using the two international parity relationships, International Fisher effect (IFE) and Purchase Power Parity (PPP). We use the regression analysis to examine the significance of change in daily interest rates and monthly inflation rates on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…If trade barriers were lifted, this would usually occur bilaterally so that the ratio of export to import prices was not strongly affected. The appreciation of the Swiss franc to most other currencies between 2009 and 2011 (Jo et al , 2016) may have had some, however limited, impact on the ratio. Similarly, changes in productivity in Switzerland during the last few decades have been more or less in pace with worldwide developments.…”
Section: Conceptmentioning
confidence: 99%
“…If trade barriers were lifted, this would usually occur bilaterally so that the ratio of export to import prices was not strongly affected. The appreciation of the Swiss franc to most other currencies between 2009 and 2011 (Jo et al , 2016) may have had some, however limited, impact on the ratio. Similarly, changes in productivity in Switzerland during the last few decades have been more or less in pace with worldwide developments.…”
Section: Conceptmentioning
confidence: 99%
“…Frenkel (1979Frenkel ( , 1981aFrenkel ( , 1981b reported that, whilst PPP did little to explain U.S. dollar versus European currency exchange rates in the short-run, PPP did perform much better as an explanatory of exchange rate behavior between sets of European currencies. Adding to Frenkel"s research and motivated by a dearth of academic literature on parity relations" validity as a predictor of daily spot rates in the short-term, Jo et al (2016), explored whether PPP and IFE were viable frameworks to predict the expected spot rate of Swiss franc against the Euro following the unpegging of the Swiss franc by the Swiss National Bank in January 2015. They concluded that whilst PPP and IFE were not perfect predictor models, they still proved very useful to gain an insight into the directional trend of spot rates in the short-term.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that whilst PPP and IFE were not perfect predictor models, they still proved very useful to gain an insight into the directional trend of spot rates in the short-term. As our study is also reviewing relationships between economic variables in Europe the observations of Frenkel (1981b) and Jo et al (2016) are particularly relevant. One conclusion Frenkel formed is that closer geographic proximity allowed lower transportation costs and, when coupled with lower trade barriers, allowed more rapid correction of exchange rates in response to changes in the inflation rate differential.…”
Section: Literature Reviewmentioning
confidence: 99%